2011
DOI: 10.1158/1078-0432.ccr-11-0783
|View full text |Cite
|
Sign up to set email alerts
|

[18F]-3′Deoxy-3′-Fluorothymidine Positron Emission Tomography and Breast Cancer Response to Docetaxel

Abstract: Purpose: To establish biomarkers indicating clinical response to taxanes, we determined whether early changes in [18 F]-3 0 deoxy-3 0 -fluorothymidine positron emission tomography (FLT-PET) can predict benefit from docetaxel therapy in breast cancer. Experimental Design: This was a prospective unblinded study in 20 patients with American Joint Committee on Cancer (AJCC) stage II-IV breast cancer unresponsive to first-line chemotherapy or progressing on previous therapy. Individuals underwent a baseline dynamic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 26 publications
1
48
2
Order By: Relevance
“…18 F-FLT PET imaging may allow tracking of therapeutic-associated cell-cycle arrest before morphologic changes become measurable. Several studies in breast, lung, and brain tumors have demonstrated that retention of 18 F-FLT correlated with tumor proliferation and have studied it for monitoring early response to therapies (95)(96)(97)(98)(99). Although 18 F-FLT has been used to image and stage several tumor types, the standardized uptake value is generally lower than that obtained with 18 F-FDG (100).…”
Section: Standardmentioning
confidence: 99%
“…18 F-FLT PET imaging may allow tracking of therapeutic-associated cell-cycle arrest before morphologic changes become measurable. Several studies in breast, lung, and brain tumors have demonstrated that retention of 18 F-FLT correlated with tumor proliferation and have studied it for monitoring early response to therapies (95)(96)(97)(98)(99). Although 18 F-FLT has been used to image and stage several tumor types, the standardized uptake value is generally lower than that obtained with 18 F-FDG (100).…”
Section: Standardmentioning
confidence: 99%
“…The kinetics of 18 F-FLT uptake in vivo reflect the level of thymidine kinase 1 activity and are thus highly associated with tumor cell proliferation (15). Previous data suggested the possibility of noninvasive tumor grading and early response assessments in patients with malignant diseases (16)(17)(18)(19)(20)(21). The results suggested that 18 F-FLT PET might predict outcomes more precisely than conventional methods in patients with nonHodgkin lymphoma (NHL).…”
mentioning
confidence: 99%
“…18 F-16a-fluoroestradiol ( 18 F-FES), 39-deoxy-39-18 F-fluorothymidine ( 18 F-FLT), and agents imaging progesterone receptors are among several that have been investigated in breast cancer imaging but have not been fully evaluated or Food and Drug Administration-approved. However, as the use of hormonal therapies and phenotyping/prevention increases, it is possible these agents will have greater application and warrant definitive study (45)(46)(47). When used in difficult clinical cases of metastatic breast cancer, information obtained from 18 F-FES PET changed management in nearly half of patients with metastatic breast cancer (47).…”
Section: Shortfalls Of Anatomic Imagingmentioning
confidence: 99%